2021
DOI: 10.3390/cancers14010201
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the TNM Classification Regarding Direct Lymph Node Invasion in Pancreatic Ductal Adenocarcinoma

Abstract: Mechanisms of lymph node invasion seem to play a prognostic role in pancreatic ductal adenocarcinoma (PDAC) after resection. However, the 8th edition of the TNM classification of the American Joint Committee on Cancer (AJCC) does not consider this. The aim of this study was to analyse the prognostic role of different mechanisms of lymph node invasion on PDAC. One hundred and twenty-two patients with resected PDAC were examined. We distinguished three groups: direct (per continuitatem, Nc) from the main tumour,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Using the TNM system, the “T” plus a letter or number (0 to 4) is used to show how far up or away from its original starting point the tumor has grown, and in the case of cancers, this means how far into the wall of the stomach. The TNM system's numerical classifications are as follows [ 19 21 ]: Tis: tumor “in situ” that is caught very early and has not grown beyond stomach lining T1: tumor has grown through lining and into connective tissue T2: tumor has grown into thick inner muscle T3: tumor has spread through outer lining but not to any nearby organs or tissues T4: tumor has spread into nearby tissues or organs …”
Section: Background Studymentioning
confidence: 99%
“…Using the TNM system, the “T” plus a letter or number (0 to 4) is used to show how far up or away from its original starting point the tumor has grown, and in the case of cancers, this means how far into the wall of the stomach. The TNM system's numerical classifications are as follows [ 19 21 ]: Tis: tumor “in situ” that is caught very early and has not grown beyond stomach lining T1: tumor has grown through lining and into connective tissue T2: tumor has grown into thick inner muscle T3: tumor has spread through outer lining but not to any nearby organs or tissues T4: tumor has spread into nearby tissues or organs …”
Section: Background Studymentioning
confidence: 99%
“…26 Lymph-node invasion is a prognostic factor for many cancers such as CRC 27 and pancreatic cancer. 28 In our study, DQB1*03 was negatively associated with lymph-node invasion in CC. Lee et al 27 reported that an increased retrieval of lymph nodes was linked to better survival in CRC.…”
Section: Discussionsupporting
confidence: 52%
“…They concluded that "direct"-only LNI patients had a similar overall survival to those with node-negative disease. Recently, other authors reported similar results [211][212][213].…”
Section: Lymph Node Metastasissupporting
confidence: 61%